ChemInform Abstract: Structure and Oxide Ion Conductivity in Tetragonal Tungsten Bronze BaBiNb5O15. Issue 46 (November 2015) - Ma, Hongqiang; Lin, Kun; Fan, Longlong; Rong, Yangchun; Chen, Jun; Deng, Jinxia; Liu, Laijun; Kawaguchi, Shogo; Kato, Kenichi; Xing, Xianran
Abstract BaBiNb5O15 is prepared by firing a stoichiometric mixture of BaCO3, Nb2O5, and Bi2O3 (1240 °C, 2 h).